Right to Appeal, Non-Treatment, and Violence Among Forensic and Civil Inpatients Awaiting Incapacity Appeal Decisions in Ontario - Radisic, Radovan; Kolla, Nathan J. (Frontiers in Psychiatry, 2019)
Background: Mental health legislation in Ontario, Canada, permits inpatients to refuse treatment while appealing their incapacity finding to the Consent and Capacity Board (CCB). Lack of treatment during this period poses safety concerns, as inpatients who remain untreated are at higher risk of engaging in violent behavior. The present study explored the relationship between non-treatment and violence among forensic and civil inpatients awaiting their CCB hearing at the largest psychiatric hospital in Canada. Methods: We investigated the electronic health records of 285 inpatients whose CCB applications were heard between 2014 and 2016 to better understand violent outcomes among inpatients and determine whether application timelines differed between forensic and civil inpatients. Results: Three key findings were observed. First, forensic inpatients had more episodes of violence requiring seclusion and restraint during the application timeline compared with civil inpatients. Second, forensic inpatients waited longer than civil inpatients for their appeal to be heard at the CCB. Finally, unwillingness to accept PRN medications and comorbid psychiatric conditions were potent risk factors for violence among all inpatients during the appeals process. Conclusions: Compared with civil inpatients, forensic inpatients waited longer for CCB appeals. They also scored higher on one measure of violent behavior. These findings provide context for the ongoing challenge of clinicians tasked with providing care for inpatients appealing findings of incapacity under mental health legislation in Ontario. We argue for a more streamlined approach to processing appeals for both forensic and civil patients. Better standardization or even revision of current mental health legislation may help eliminate clinical disparities between patient groups.